Intravenous therapy device labeling in Intensive Care Units: an integrative review - Geovane de Kassio Nunes; Juliana Faria Campos; Rafael Celestino da Silva (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to synthesize the evidence on intravenous device labeling used to identify medications administered to patients in Intensive Care Units, with a view to preventing medication errors. Methods: an integrative review, in the LILACS, IBECS, Embase, MEDLINE, Scopus, Web of Science and CINAHL databases, from November to December 2021, using descriptors and selection criteria. Data were collected in 11 articles and subsequently classified, summarized and aggregated. Results: pre-designed labels, with pre-defined colors and information, help to prevent medication identification errors. There is still a lack of standardization in the practice of labeling syringes, intravenous lines, infusion pumps and saline solution bags. There are errors related to the lack of labeling devices or to their performance with incomplete information. Conclusions: device labeling is a barrier to defending the medication system safety and should be standardized.